Gestational Hypertension and Preeclampsia in Living Kidney Donors. Issue 5 (May 2015) - Garg, Amit X.; Nevis, Immaculate F.; McArthur, Eric; Sontrop, Jessica M.; Koval, John J.; Lam, Ngan N.; Hildebrand, Ainslie M.; Reese, Peter P.; Storsley, Leroy; Gill, John S.; Segev, Dorry L.; Habbous, Steven; et al.
<x xml:space="preserve">Abstract</x> ABSTRACT Currently, the majority of living kidney donors are women, and these young-women donors are often concerned about the possible effect of kidney donation on future pregnancies. Animal studies have shown evidence of higher blood pressure and urinary protein excretion in animals with 1 kidney compared with animals with 2. However, human studies that have compared donors with healthy nondonors during pregnancy have yielded conflicting results. In this retrospective, matched-cohort study, the authors compared kidney donors to matched, healthy nondonors with regard to risk of developing gestational hypertension or preeclampsia, as well as other maternal and fetal outcomes. They used databases in Ontario to compare pregnancy outcomes in 85 eligible women who donated a kidney between 1992 and 2010 with 510 healthy, nondonors. Baseline characteristics compared were age at the time of cohort entry, urban or rural location, income, the number of pregnancies at 20 weeks' gestation at cohort entry, and time to first pregnancy after cohort entry. The primary outcome was obtained from diagnostic codes for gestational hypertension or preeclampsia; secondary outcomes examined more specifically other maternal and fetal outcomes. Over an approximately 11-year period, 595 women were followed up through their pregnancies. Donors and nondonors had the same number of doctor visits during pregnancy, but gestational hypertension or preeclampsia was higher among donors (11% vs 5%; odds ratio for donors, 2.4; 95% confidence interval, 1.2–5.0; P = 0.01). Secondary outcomes revealed no significant difference in the rate of preterm birth (8% vs 7%) and low birth weight (6% vs 4%). There were no reports of miscarriage, stillbirth, or maternal death in either group. The risks of gestational hypertension or preeclampsia are higher in kidney donors than in nondonors with similar baseline health.